Contribution to the morphological description of the marine leech, Ozobranchus margoi (Apáthy) (Rhynchobdellida: Ozobranchidae) by using combined histology, micro-CT and SEM - Cascarano, Maria Chiara; Keklikoglou, Kleoniki; Arvanitidis, Christos; Katharios, Pantelis (Zootaxa, 2017)
The ozobranchid leech, Ozobranchus margoi (Apáthy, 1890), parasite of the loggerhead turtle, Caretta caretta (Linnæus), was described through a multilevel approach including three different techniques: scanning electronic microscopy, histology and micro-CT. New insights are provided concerning the structure of the sensilla on the body, the eyes with emphasis on the structure of photoreceptors, the digestive system and the reproductive organs.